Identification of Lactic Acid Bacteria (LAB) from pre-fermented liquids of selected cereals and legumes and characterization of their exopolysaccharides (EPS) - Yalmanci, Dilara; Ispirli, Humeyra; Dertli, Enes (ELSEVIER, 2022)
Recently, isolation of Lactic Acid Bacteria (LAB) strains with important technological functions from plant-based products has gained special interests related with the increment of consumer preferences to the plant-based fermented products. In this context, various cereals and legumes that were underwent to germination or not were selected for the isolation of exopolysaccharide (EPS) producer LAB strains in this study. Following geno-typic discrimination, 17 distinct strains belonging to Weissella confusa, Weissella cibaria, Lactococcus lactis subsp. hordniae, Leuconostoc lactis, Lactiplantibacillus plantarum and Leuconostoc mesenteroides were identified from pre -ferment liquids. Two strains Weissella confusa W-16 and Leuconostoc lactis GW-6 were the highest EPS producers, and their EPSs were further characterized. The 1H and 13C NMR results revealed that both strains were dextran producers containing (1 -> 3)-linked alpha-D-glucose units as branches with 9.2% and 6.9% levels for Weissella confusa W-16 and Leuconostoc lactis GW-6, respectively. FTIR analysis also supported the dextran structure and demonstrated the functional groups within the dextrans. A high level of thermal stability was observed in both dextrans detected by TGA and DSC analysis. Both dextrans were in amorphous characteristics determined by XRD analysis. These findings demonstrate that pre-fermented liquids of different cereals and legumes can be source of technologically important LAB strains with EPS production characteristics.
Keywords: Fermentation; Legumes and cereals; Postbiotics; Exopolysaccharides (EPS); PHYSICOCHEMICAL PROPERTIES; FUNCTIONAL-PROPERTIES; ANTIOXIDANT ACTIVITY; WEISSELLA-CONFUSA; DEXTRAN; SOURDOUGH; BIOACTIVITIES; BIOSYNTHESIS; PURIFICATION; GERMINATION; Food Science & Technology